Efektivitas Program Pemberdayaan Usaha Mikro, Kecil, dan Menengah (UMKM) Dinas Koperasi dan UKM di Kabupaten Kolaka - Hafsha; La Ode Asrun Azis. R; Muhammad Hidayat Djabbari (Jurnal Ilmiah Administrasita', 2025)
The purpose of this study is to determine the effectiveness of the Micro, Small, and Medium Enterprises (MSME) Empowerment Program implemented by the Office of Cooperatives and MSMEs of Kolaka Regency. This research employs a descriptive research type with a qualitative approach. The study was conducted at the Office of Cooperatives and MSMEs of Kolaka Regency. The informants in this research consisted of the Head of the Office of Cooperatives and MSMEs of Kolaka Regency, the Head of the Micro Business Empowerment Division, office staff, as well as MSME actors who have participated in training, mentoring, and coaching activities within the MSME empowerment program. The types and sources of data used include primary data and secondary data. The results of the study indicate that the MSME empowerment program in Kolaka Regency has not been fully effective. In terms of target accuracy, most program recipients are small business actors who require support; however, some recipients were found to not fully align with the targeted criteria. Regarding the socialization aspect, information dissemination has not been optimal because it has not reached all MSME actors. In the aspect of program goal achievement, training activities have increased entrepreneurs’ knowledge, but they have not significantly impacted income improvement and business independence due to the lack of follow-up mentoring. Meanwhile, the program monitoring aspect has not been carried out systematically because of the absence of a structured evaluation mechanism. Supporting factors of the program include local government support, inter-agency collaboration, and the participation of MSME actors. Inhibiting factors include budget limitations, insufficient comprehensive socialization, and a weak monitoring and evaluation system after the program implementation. Overall, the MSME empowerment program in Kolaka Regency is considered ineffective and requires improvements in socialization, follow-up mentoring, as well as the program’s monitoring and evaluation system.